The Internalization of Islamic Eco-Theological Values in Eco-Pesantren Practices at the Agro Nurul Islam Islamic Boarding School in Batam - Ardiansyah, Heru; Rozi, Syafwan (AL-ADYAN, 2026)
The ecological crisis underscores the importance of developing an environmental education model based on religious values, one of which is through the concept of eco-pesantren. This study aims to analyze the practice of Islamic eco-theology in the development of an eco-pesantren at the Agro Nurul Islam Galang Batam Islamic Boarding School through the internalization of the values of tawhid, khalifah, amanah, and mizan. The study employs a qualitative approach with a field research design. Data were collected through participatory observation, semi-structured interviews with the pesantren leadership, teachers who also manage the environmental program, and students actively involved in ecological activities, and were supported by documentation. Data analysis was conducted through data reduction, data presentation, drawing conclusions, and validation using source and method triangulation. The results indicate that the eco-pesantren is implemented in an integrated manner through religious education, agricultural practices, reforestation, a culture of simple living, and the management of the pesantren’s environment. The internalization of the values of tauhid, khalifah, amanah, and mizan shapes the students’ environmental awareness and ethics, leading them to view nature conservation as part of their worship and moral-religious responsibility. This study affirms that the eco-pesantren is a form of Islamic eco-theological praxis that contributes to building spirituality-based environmental education and can serve as a model for strengthening ecological awareness in Islamic educational institutions.